Dexibuprofen Therapeutic Advances: Prodrugs and Nanotechnological Formulations - Anna Gliszczyńska; Elena Sánchez-López (MDPI AG, 2021)
S-(+) enantiomer of ibuprofen (IBU) dexibuprofen (DXI) is known to be more potent than its R-(−) form and exhibits many advantages over the racemic mixture of IBU such as lower toxicity, greater clinical efficacy, and lesser variability in therapeutic effects. Moreover, DXI potential has been recently advocated to reduce cancer development and prevent the development of neurodegenerative diseases in addition to its anti-inflammatory properties. During the last decade, many attempts have been made to design novel formulations of DXI aimed at increasing its therapeutic benefits and minimizing the adverse effects. Therefore, this article summarizes pharmacological information about DXI, its pharmacokinetics, safety, and therapeutic outcomes. Moreover, modified DXI drug delivery approaches are extensively discussed. Recent studies of DXI prodrugs and novel DXI nanoformulations are analyzed as well as reviewing their efficacy for ocular, skin, and oral applications.